Dune. House Harkonnen. Volume one - Herbert, Brian; Anderson, Kevin J., 1962- (BOOM! Studios, 2023)
"Delve into the past of Gurney Halleck, Leto Atreides, Lady Jessica, and Liet Kynes, and discover how the complex and brutal machinations of House Harkonnen shaped their future! What difficult choices will tear Leto apart as Baron Harkonnen plots against not just House Atreides, but the Bene Gesserit and the Emperor himself? And who watches Duke Atreides from afar? This dangerous figure holds untold significance for his future and lineage... The second NYT Bestselling prequel to Dune is adapted for the first time by award-winning novelists Brian Herbert and Kevin J. Anderson and artist Michael Shelfer (Domino), unveiling a closer look at the rising conflict between beloved characters and bitter villains."--Amazon.com.